Family support and the healthcare workforce when the patient chooses a cesarean section on maternal and neonatal outcomes - Arien Dwi Ajeng Adhe Safitri; Andriyanti Andriyanti; Dwi Izzati Budiono (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Childbirth is a series of pregnancy processes that end with the expulsion of the products of conception. The number of births with SC is increasing every year. In Indonesia, the incidence of cesarean section in 2009 has reached 29.6%. This number certainly affects the mortality and morbidity rates in subsequent deliveries.Purpose: To identify family support and the healthcare workforce when the patient chooses a cesarean section on maternal and neonatal outcomesMethod: A case study with TOLAC (Trial of Labor After Cesarean Delivery) is a planned effort to give birth vaginally by a woman who has had a previous SC delivery. Women's perceptions related to pregnancy to delivery can influence the choice of the desired delivery method.Results: Women 31 year old with G3P1011 assisted since 17-18 weeks of gestation. Had an obstetric history with 1x caesarean section in 2016 because there was no progress in labour. Early referral planning has been carried out. Termination of pregnancy by sectio caesarea is planned at 38-39 weeks of gestation. Since the beginning of the pregnancy, the mother wanted to give birth vaginally, but the mother did not get support from her husband or family. Before the intervention was carried out, the mother experienced signs of labor and the mother wanted to try vaginal delivery but was not supported by healthcare workforce and a cito SC was performed. The baby was born healthy with a good Apgar score.Conclusion: The perceptions and beliefs that pregnant women have after SC surgery need to be balanced with the support of their families and healthcare workforce so that they are successful in undergoing trials of the normal delivery method according to preference. Mentoring activities can be a method of providing education, monitoring efforts, and early detection of complications in pregnant women with former SC operations.